Antimicrobial Screening of some Medicinal Plants against Selected Bacterial Species - Sapkota, Pragya; Bhattarai, Sapana; Bajracharya, Anup Muni; Lakhe, Pramesh Bahadur; Shrestha, Nishant (Scientific World, 2020)
Medicinal plants are used as traditional treatment for numerous human diseases. According to WHO, medicinal plants would be the best source to obtain a variety of drugs. Contrary to the synthetic drugs, antimicrobial of plant origin are not associated with many side effects and have an enormous therapeutic potential to heal many infectious diseases. Present study was carried out on the screening of some medicinal plants against selected pathogenic organisms in the period of October 2017 to January 2018. A total of nine different medicinal plants were screened and evaluated for their antimicrobial activity against 10 bacterial species. Among them, Euphorbia hirta, Azadirachtaindica, Artemisia vulgaris were found to be effective against gram positive bacteria (Bacillus subtilis, Staphylococcus aureus, Methicillin resistant Staphylococcus aureus MRSA), whereas rest six medicinal plants (Aeglemarmelos, Justiciaadhatoda, Ficusreligiosa, Syzygiumcumini, Nyctanthes arbor and Meliaazedarach) were found to be ineffective against all the microorganisms (Bacillus subtilis, Escherichia coli, Klebsiellapneumoniae, Proteus vulgaris, Pseudomonas aerogenosa, Salmonella typhii, Shigelladysentriae, MRSA). The minimum bactericidal concentration (MBC) of Euphorbia hirta against Bacillus subtilis and Staphylococcus aureus was found to be 12.5mg/ml and MBC of Artemisia vulgaris against Bacillus subtilis and MRSA was also found to be 12.5 mg/ml while of Staphylococcus aureus was 25mg/ml. Similarly, the MBC of Azadirachta indica against Staphylococcus aureus was 25mg/ml.